An evolved native microalgal consortium-snow system for the bioremediation of biogas and centrate wastewater: Start-up, optimization and stabilization. (15th May 2021) - Qiu, Shuang; Yu, Ziwei; Hu, Yanbing; Chen, Zhipeng; Guo, Jianhua; Xia, Wenhao; Ge, Shijian
Highlights: ROS reduction improved ENMC adaptation in CW by gradual stress increase strategy. Supplementation of snow and biogas enhanced approximately 10% ENMC growth in CW. An ENMCS system was established and operated for 310-day treating CW and biogas. Optimum condition: 50% fill ratio, 24 h feeding, 6 d HRT, 70-FCW+30-SN, open-PBR. ENMCS was effective for bioremediation of AD effluents and biomass production. Abstract: It is necessary to develop sustainable technologies for centrate wastewater (CW) and biogas treatment from sludge anaerobic digestion (AD) systems in an environmentally friendly and economical manner. The microalgae-based bioremediation approach presents a competitive alternative due to its capacity for nutrient recovery and carbon sequestration. However, process instabilities and operating challenges limit its development and implementation largely due to the complexities in the CW and biogas. In this study, the evolved native microalgal consortium (ENMC) was firstly developed using the gradual stress increase method to enhance their adaptation in high ammonium condition. The supplementation of local snow (with Ca 2+ and Mg 2+ ) and biogas into CW significantly enhanced ENMC growth through batch tests. Subsequently, an integrated ENMC-snow (ENMCS) system was proposed consisting of a hydrolysis-acidification reactor (HAR), biogas upgrade reactor, and photobioreactor (PBR). The ENMCS system was systematically investigated under both batch and semi-continuous operations, by adjusting primary process parameters including the fill ratio, feeding time, hydraulic retention time (HRT), wastewater pretreatment, and PBR type. It was eventually optimized as a 24 h, 70% fermented CW diluted with 30% snow water, semi-continuous feeding system with a fill ratio of 50% and HRT of 6 d in an open-PBR. Long-term operation (310 days) showed superior biomass yield (0.3059 ± 0.0039 g/(Ld)) and nutrient removal efficiencies (95.6 ± 0.13% and 90.8 ± 0.44% for NH4 + -N and PO4 3− -P removal). Meanwhile, biogas was upgraded with an 82.2% CO2 reduction. The economic and environmental analysis further demonstrated the ENMCS system as an effective alternative for the bioremediation of AD effluents while simultaneously producing value-added biomass, especially applicable to snowy regions. Graphical abstract: Image, graphical abstract